2017
DOI: 10.1038/s41598-017-03019-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-large non-volatile modulation of magnetic moments in PbZr0.2Ti0.8O3/MgO/La0.7Sr0.3MnO3 heterostructure at room temperature via interfacial polarization mediation

Abstract: Multiferroic hybrid structures PbZr0.2Ti0.8O3 (PZT)/La0.7Sr0.3MnO3 (LSMO) and PZT/MgO/LSMO were epitaxially deposited on (001) Nb:SrTiO3 crystals. Crystallinity and ferroelectric domain structures were investigated for the PZT/LSMO heterostructure. Interestingly, relatively high non-volatile magnetoelectric coupling effects were observed in both heterostructures at room temperature. The change of chemical valence for Mn and Ti at the PZT/MgO/LSMO interface may play a dominant role rather than external strain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…[15][16][17][18][19] In such layered FE/FM heterostructures where the LSMO layer also serves as the bottom electrode, the ME coupling relies on either the interfacial strain or the charge ordering between the layers. [20][21][22] In particular, LSMO/BTO multilayered thin films can exhibit strong ME coupling, as each layer can sustain its ferroic orders at room temperature and above. [23][24][25][26] Eerenstein et al reported a giant ME coupling constant, α∼ 2.3 × 10 −7 s m −1 , in a ME BTO/ LSMO epitaxial thin film heterostructure of around 200 K temperature, near the rhombohedral to orthorhombic (R-O) phase transition of BTO.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] In such layered FE/FM heterostructures where the LSMO layer also serves as the bottom electrode, the ME coupling relies on either the interfacial strain or the charge ordering between the layers. [20][21][22] In particular, LSMO/BTO multilayered thin films can exhibit strong ME coupling, as each layer can sustain its ferroic orders at room temperature and above. [23][24][25][26] Eerenstein et al reported a giant ME coupling constant, α∼ 2.3 × 10 −7 s m −1 , in a ME BTO/ LSMO epitaxial thin film heterostructure of around 200 K temperature, near the rhombohedral to orthorhombic (R-O) phase transition of BTO.…”
Section: Introductionmentioning
confidence: 99%